2018
DOI: 10.1177/1557988318783504
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Enhancing Drugs Abuse Caused Cardiomyopathy and Acute Hepatic Injury in a Young Bodybuilder

Abstract: A number of performance-enhancing drugs (PEDs) are used illicitly to improve muscle strength by the bodybuilders. The misuse of these drugs is associated with serious adverse effects to different organs. A previously healthy 22-year-old male bodybuilder after taking stanozolol, clenbuterol, and triiodothyronine for 10 days presented to the hospital with symptoms of icteric sclera, progressive dyspnea, intermittent cough, and bloody sputum. He was diagnosed with dilated cardiomyopathy and acute hepatic injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…Liver was enormously enlargedChemoembolization was declined by patient who was recommended for transplantation [118]AustraliaCRHepatocellular carcinomaSurgery [119]LebanonCRLiver injury resulting in prolonged cholestasis and acute kidney injuryAdvice to discontinue AAS, medical therapy, plasma exchange. Patient refused renal biopsy. [120]ChinaCRDilated cardiomyopathy and acute hepatic injuryMedical therapy [121]PolandCRSevere intrahepatic cholestasis that developed to severe liver failureMedical therapy [122]UKCSCholestasisMedical therapy [123]SpainCRSevere cholestatic jaundiceUnclear [124]USACSSevere hepatotoxicity, cholestasisMedical therapy [125]NetherlandsCRMild jaundice; cholestatic hepatitis identified through liver biopsyMedical therapy [126]UKCRThree grade II oesophageal varicesBlood transfusion and sclerotherapy [127]AustraliaCRIntrahepatic cholestasisMedical therapy [128]USACRSevere cholestasis and renal failure. Re-admitted with pruritusMedical therapy [129]SpainCRHepatic rupture, liver failure.…”
Section: Resultsmentioning
confidence: 99%
“…Liver was enormously enlargedChemoembolization was declined by patient who was recommended for transplantation [118]AustraliaCRHepatocellular carcinomaSurgery [119]LebanonCRLiver injury resulting in prolonged cholestasis and acute kidney injuryAdvice to discontinue AAS, medical therapy, plasma exchange. Patient refused renal biopsy. [120]ChinaCRDilated cardiomyopathy and acute hepatic injuryMedical therapy [121]PolandCRSevere intrahepatic cholestasis that developed to severe liver failureMedical therapy [122]UKCSCholestasisMedical therapy [123]SpainCRSevere cholestatic jaundiceUnclear [124]USACSSevere hepatotoxicity, cholestasisMedical therapy [125]NetherlandsCRMild jaundice; cholestatic hepatitis identified through liver biopsyMedical therapy [126]UKCRThree grade II oesophageal varicesBlood transfusion and sclerotherapy [127]AustraliaCRIntrahepatic cholestasisMedical therapy [128]USACRSevere cholestasis and renal failure. Re-admitted with pruritusMedical therapy [129]SpainCRHepatic rupture, liver failure.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al reported a case of a healthy 22-year-old male bodybuilder that developed acute hepatic injury and rapidly progressive dilated cardiomyopathy after using stanozolol for 10 days [18]. This raises the question of how many younger athletes are at risk.…”
Section: Cardiomyopathy and Asmentioning
confidence: 99%
“…As well as reducing body fat and body weight, it also retains both muscle mass and body strength at the same time. Many bodybuilders, performance athletes, and those wanting to lose weight currently use the drug (11,28,29).…”
Section: Discussionmentioning
confidence: 99%